The Federal Republic of Germany and the Western Aliance at the Time of the Berlin Crisis (Czech Journal of International Relations, 1966)
The renewed German imperialist state remained only the torso of the Third Reich. Neither the economic upturn nor remilitarization fundamentally changed its position of power in Europe. The former great power, aspiring to European and world hegemony, remains a power of the second order.